Edukasi 3m Sebagai Anticipatory Guidance Terhadap Penularan Covid-19 Pada Anak Dengan Tuna Grahita - Fika Nur Indriasari (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2021)
The current covid-19 pandemic has made people concerned due to this virus has spread out to many countries. Preventive action are required to prevent the potential spread out of Covid-19. One of the action taken is the protection of children and educational facilities in schools by educating 3M to implement health protocols. The methods used in this activity are lectures and simulations. The media used are educational videos. This activity was carried out at SLB N Pembina Yogyakarta with 24 student with mild and moderate retardation mental. The results of the activity showed that there was an increase in knowledge in the good category by 25%. This shows that the combination of audiovisual and simulation is effective to increase the knowledge and skills of children with mental retardation. Education and assistance from teachers and parents is required to maintain children's understanding in the application of health protocols so the risk of covid-19 transmission will be minimal. Keywords: 3M education, Anticipatory Guidance, Covid-19, Children with Intelectual disability